Knowledge and attitudes related to the COVID-19: role of media communication and emotional factors. (20th October 2021) - Covolo, L; Della Vedova, AM; Croce, M; Zamperoni, S; Nanni, A; Sorosina, S; Gelatti, U
Abstract: Background: The COVID-19 pandemic was characterized by difficult communication challenges due also to scientific uncertainty regarding the nature and management of the new coronavirus. The aim of the study was to assess the impact of media information on the population's COVID-19-related knowledge, behavior and emotional state. Methods: In a cross-sectional study, data from July to September 2020 was collected via survey posted on social media (SM). It included also an analysis of participants' e-health literacy (e-HEALS), and depression, anxiety, and stress symptoms using DASS-21 tool. Results: Of the 2, 140 subjects, as a main source of information, 69% indicated institutional websites and 26% SM. Fifty-four percent believed expert information to be crucial in changing their behavior. However 30% of health professionals (HP) and 37% of non-HP found expert (scientists) communication hard to understand. Despite high education level (44.3% graduates), 19% denied knowing of the virus origin. Others believed the human manipulation theory (33% of the total and 29% of HP). The e-HEALS score in these subjects was lower than those reporting the natural origin of virus (28.4 ± 6.2 vs 30.5 ± 6.1, p<.001). Young people aged <35 y reported signs of depression (41%), anxiety (28%) and stress (36%) more than older participants (p=.0001). As for infection concern, it was higher in females (58% p<.001), those not living alone (56% p<.01), those living with a senior (62% p<.01) or with those at high risk of COVID-19 (64%p<.001). Greater worry meant stricter guideline adherence (hand washing 56% p<.0001; surface sanitation 42% p<.0001; social distancing 77% p<.0001) and mask usage before mandate (45% p<.0001). Conclusions: Although the sample was overall well informed and followed preventive measures, institutional communication was found to be confusing especially by experts. The findings highlighted the strong psychological impact on the community, young people especially. Key messages: The study confirms the importance of putting effort on population health literacy and more effective institutional communication strategies. Proactive and timely psychological interventions should be provided to address the mental health needs of the population resulting from the pandemic.